Upaya Meningkatkan Kemampuan Membaca Kalimat Sederhana Melalui Penggunaan Media Kartu Kata Berseri dengan Layanan Penguasaan Konten pada Anak Didik TK Islam - Jumatriadi Jumatriadi (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2017)
This research is aimed to know the increases of simple sentences reading ability on the use of card media with content mastery services to students of TK Islam. The setting of this research was at B Group of TK Islam Attohiriyah Keruak. The kind of this research is clasroom action research. The technique used in cellecting data is observation and test. The gained data was descipted and analyzed with quantitative descriptive technique.The researcher gets that there was the increase of ability of comprehending simple sentences card media with content mastery services to significantly at students of the B Group of TK Islam At-Thohiriyah Keruak Academic year 2016/2017.